Carcass and meat quality characteristics of purebred (hair) and crossbred (wool × hair) sheep lambs grazing fescue pasture as influenced by breed type, sex, and supplementation - Jung Hoon Lee; Stephan Wildeus; Beruk Berhane Lemma; Brou Kouakou (Journal of Applied Animal Research)
The influence of breed type (purebred vs. crossbred), sex (short-scrotum ram vs. ewe lamb), and supplementation (pasture-only vs. pasture plus 2% soy hull) on carcass and meat quality of landrace hair (Barbados Blackbelly; BB and St. Croix; SX) and wool (Dorset; DO) × hair sheep lambs was evaluated. Forty-eight, mixed sex 5-mo old purebred hair (body weight (BW) = 17.9 ± 1.95 kg) and crossbred (wool × hair) sheep lambs (BW = 21.7 ± 2.56 kg) rationally grazed predominantly tall fescue pasture during summer with or without soy hull supplementation at 2% of BW. At the end of a 90-d grazing trial, lambs were harvested using the USDA standard procedures and their carcasses were evaluated. After 24 h chilling storge (2°C), longissimus muscle (LM) pH was measured, and carcasses were fabricated into primal cuts. Loin chops and fat depots were collected to analyse meat quality parameters. Supplementation rather than crossbreeding had more significant effect on carcass quality under the conditions of this experiment. Regardless of breed type, soy hull supplementation improved colour, lipid oxidation stability and texture properties of fresh lamb, whereas pasture-only lambs had healthier fatty acid profiles compared with those from supplemented lambs.